Assessing structural resilience of masonry chamber-housed substations subject to flood flow and debris impact - Wenzhu Li; Lee S. Cunningham; David M. Schultz; Sarah Mander; Chin Kim Gan; Mathaios Panteli (Innovative Infrastructure Solutions, 2025)
Chamber-housed substations are a common substation type, essential for voltage regulation, load balancing, and fault isolation to ensure power supply grid stability and reliability. As typically ground-based structures, chamber-housed substations are vulnerable to damage from flooding. In the case of chambers constructed from plain masonry, these may be susceptible to structural damage from forces generated by flood flows. Although previous studies have examined substation failures based on flood levels, they often overlook the structural damage caused by moving floodwaters and floating debris, thereby underestimating risks and overestimating substation resilience. The present study introduces an analytical framework that uses computational fluid dynamics (CFD) coupled with finite element (FE) analysis to predict flood forces and structural responses in a level of detail that would hitherto not be possible with existing design code approaches. The CFD-based modelling approach was validated against existing hydraulic experiments and subsequently applied to a case study of a typical masonry chamber-housed substation in Malaysia, a country prone to severe annual flooding. The results reveal that substation walls can withstand flood velocities up to 10 m/s without debris. However, the presence of debris leads to damage at velocities below 2 m/s, highlighting a significant reduction in resilience. Fragility and risk curves, derived from a normalised Weibull function, further reveal that ignoring debris impact underestimates forces on walls by 60% to 83%. These findings highlight the need to update design guidelines to account for debris impact and to develop suitable retrofitting strategies for existing chambers.

Resilient generation planning considering long periods of low-RES output - Ektor-Ioannis Stasinos; Mathaios Panteli; Nikos Hatziargyriou (Environment Systems and Decisions, 2025)
The growing concerns over mitigating climate change effects resulted in power system planning and generation expansion strategies that aim in increasing penetration of intermittent renewable energy sources (RES) to fulfill the national energy and climate plans (NECPs) of countries worldwide. However, the variable and intermittent nature of RES output, compounded by uncertainties arising from climatic and weather changes, poses significant challenges. These challenges necessitate careful consideration in generation planning and in determining the operational reserves of RES-rich power systems to ensure resilience. This paper employs a generation capacity operational planning method based on the Screening Curve Method (SCM), assuming various levels of large RES penetration and diverse spinning generation reserve policies, necessary to cope with various levels of RES generation deficits, to guarantee power system resilience. The proposed approach can be used to assess the overall reduction of capacity and decommissioning of thermal units, while ensuring resilient operation against various levels of annual RES generation deficits. Furthermore, an approximation of the total annual system operation cost is also provided, considering the impact of the employed spinning reserve policies.

Conflict-resilience framework for critical infrastructure peacebuilding - Stergios-Aristoteles Mitoulis; Sotirios Argyroudis; Mathaios Panteli; Clemente Fuggini; Sotirios Valkaniotis; William Hynes; Igor Linkov (Sustainable Cities and Society, 2023)